Strategi Promosi Pengurus POKJAR Mandiri Pemalang dalam Menjaring Calon Mahasiswa Baru Universitas Terbuka di Era Society 5.0 - Sunarya, Amud; Riau, Dwi Putranto; Yuliani, Isnaeni; Salmon, Indra Pratama Putra; Sari, Jayanti Armida; Antoro, Aji Fajar Suryo; Diana, Bambang Agus (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The AIDAS promotion model (Attention, Interest, Desire, Action, Satisfaction) is a strategy carried out by the Mandiri Pemalang Open University (UT) Study Group (POKJAR) to attract new students. The purpose of this study was to analyze the promotion strategy carried out by the POKJAR Mandiri Pemalang management in recruiting new students to increase the number of UT students and what obstacles were faced by the POKJAR Mandiri Pemalang management in carrying out their promotion strategy. The research was carried out using a qualitative descriptive approach, with data collection techniques through surveys, observations, interviews, and study documentation related to the research. The data analysis technique uses interactive analysis which starts with data collection, reduction, presentation, and conclusion. The results of the research analysis showed that the Managers of the POKJAR Mandiri Pemalang Promotion Strategy who used the AIDAS model in general could be implemented it well. Aspects of attention, creating digital platforms for Instagram, Facebook, and websites as promotional media. Aspects of interest, opening a stand at Car Free Day (CFD) activities and working with schools in Pemalang Regency to carry out promotions. Aspects of desire, utilizing alumni or students to carry out socialization and promotion. The action aspect, assisting students who have limited learning tools or others. Satisfaction aspect, feeling happy and grateful to prospective students who have successfully registered at UT. The obstacles faced are the vast area of ​​Pemalang Regency so that social prom activities in schools are less accessible, limited budgets for conducting social prom, the existence of hoax news from individuals who spread skewed information about UT, there is a feeling of being underappreciated or there is no shade as a representative from UT by the management of POKJAR and SALUT.